WEDGE MADE OF PAPER AND CARDBOARD DERIVATIVE MATERIAL AND PRODUCTION METHOD - ACARGIL, Hasan; IZGIN, Fethi (2025)
The subject matter of this invention is related to wedges used in the assembly, transportation, fixation, support, and protective packaging of products or materials produced in industrial sectors, and its production method. The wedges subject matter of the invention are 100% recyclable and are especially made from laminated, paper glued together, and cardboard derivatives. La présente invention concerne des cales utilisées dans l'assemblage, le transport, la fixation, le support et l'emballage protecteur de produits ou de matériaux produits dans des secteurs industriels, et leur procédé de production. Les cales objet de l'invention sont recyclables à 100 % et sont notamment fabriquées à partir de papier laminé collé et de dérivés de carton.